PENGARUH KUALITAS PELAYANAN DAN NILAI NASABAH TERHADAP KEPUASAN NASABAH ( Studi Kasus pada Nasabah Produk Tabungan Simpedes BRI Unit Tugu Semarang) - Setiarini, Dita Septi; Nurseto, Sendhang (Jurnal Ilmu Administrasi Bisnis, 2017)
offer services but also products offered by the bank. Simpedes is one of the savings products offered by BRI for the village community which then extends to the urban community using the savings products. However, customers of Simpedes savings product at BRI Unit Tugu Semarang have decreased. This is due to several complaints on customer ratings on Simpedes product services. This study aims to determine the effect of service quality and customer value on customer satisfaction in customers of savings products Simpedes BRI Unit Tugu Semarang.This type of research is explanatory research, the method of data collection using interviews, data collection tools using a questionnaire with a sample of 100 respondents, customers are saving on Simpedes savings products. The sampling technique by purposive sampling. Data were analyzed by using validity test, reliability test, coefficient of determination, simple linear regression, multiple linear regression, T test, and F test with the help of SPSS 16.0 program.The results of this study can be concluded that partially these variables have a significant effect on customer satisfaction. Service Quality affects customer satisfaction with t count (7,568)> t table (1,9845). The value of customer influence on customer satisfaction with t count (8,373)> t table (1,9845). Simultaneously, the variable of service quality and customer value have an effect on customer satisfaction with result of F count (73,837) > F table (3,0902).Suggestions that can be given in the research is the BRI Tugu Unit need to improve the service quality by adding employees who assist customer transactions at the teller, adding facilities for space services such as chairs and drinking water and provide attractive interest rates on Simpedes savings products.